Food demand elasticities in Argentina, Paraguay and Bolivia. Econometric estimation from household surveys - Lema, Daniel (2007)
This paper presents the methodology and estimation of food demand elasticities for Argentina, Paraguay and Bolivia using household survey data. The paper reviews the theoretical and empirical approach behind the applied food demand estimation. The empirical approach consists in the estimation of a censored corrected LinQuad incomplete demand system using microdata from national household surveys. The empirical implementation and results are consistent with the state of the art in applied demand estimations using censored cross sectional data.